Analisa Program Magang Inkubator Kerja di TVKU Semarang dalam Pembentukan Kompetensi dan Pengalaman Profesional Bagi Mahasiswa - Retnaningtyas Niken Hapsari; Hapsari Dwiningtyas Sulistyani (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
In accordance with the Ministry of Research, Technology, and Higher Education (Kemenristekdikti) Press Release Number: 3/SP/HM/BKKP/I/2019, themed “Open, Flexible, and Quality Research, Technology, and Higher Education,” it is stated that there is a current need for efforts to prepare higher education graduates. This preparation focuses on ensuring they possess the required competencies, work capabilities, and professional attitudes, which are to be achieved through certification, the enhancement of student achievements, and the provision of professional experience. TVKU, known as a local television station in the Semarang region, offers an internship program known as an “incubator.” This study aims to understand the significance of the role of this television incubator program in developing the competencies and professional experience of students at Universitas Dian Nuswantoro Semarang before they complete their studies and enter the actual workforce. The method applied in this study is the descriptive historical method. Data for this study was obtained through field research, which included interviews, observation, and documentation. Data analysis was conducted using a descriptive qualitative analysis method, based on the stages of data collection, data reduction, data display, and data verification. The study’s findings indicate a correlation between the TVKU work incubator program and the development of students’ competencies and professional experience. This is evidenced by the success of alumni in obtaining employment in their desired fields after participating in the incubator program.